2011
DOI: 10.1111/j.1365-2850.2011.01781.x
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain and lipid–glucose profiles among patients taking antipsychotic medications: comparisons for prescriptions administered using algorithms versus usual care

Abstract: The purpose of this study was to determine if treatment strategy had a significant effect on the occurrence of physiological changes consistent with metabolic syndrome and/or type 2 diabetes in patients using atypical antipsychotic medications. The four variables assessed were: weight gain, fasting blood sugar, triglycerides and cholesterol. The two strategies compared were (1) evidence-based practice, derived from the Texas Medication Algorithm Project, and (2) practitioner preference. A retrospective chart r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…We did not provide data on current monitoring practices but noted that some authors found a lack of monitoring, especially for schizophrenic patients, which has to be overcome as soon as possible [103]. Others have shown that the implementation of monitoring guidelines resulted in an improvement of monitoring practice, and following evidence-based guidelines seems to be beneficial with regard to weight gain [104]. Evidence-based guidelines for monitoring risk factors in children, adolescents and adults already exist and should be followed [105].…”
Section: Monitoring Weight Gainmentioning
confidence: 78%
“…We did not provide data on current monitoring practices but noted that some authors found a lack of monitoring, especially for schizophrenic patients, which has to be overcome as soon as possible [103]. Others have shown that the implementation of monitoring guidelines resulted in an improvement of monitoring practice, and following evidence-based guidelines seems to be beneficial with regard to weight gain [104]. Evidence-based guidelines for monitoring risk factors in children, adolescents and adults already exist and should be followed [105].…”
Section: Monitoring Weight Gainmentioning
confidence: 78%
“…La dislipidemia y la diabetes mellitus son frecuentes en los pacientes que consumen antipsicóticos, condición importante, ya que los antipsicóticos atípicos pueden alterar el metabolismo de lípidos y carbohidratos, y, por lo tanto, se hace necesario evaluarlos adecuada y más frecuentemente para evitar la pérdida de control metabólico de estas enfermedades asociadas (28,29).…”
Section: Discussionunclassified